2021
DOI: 10.1108/jeim-06-2021-0238
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental ties or expressive ties? Impact mechanism of supervisor–subordinate ties based on enterprise social media on employee performance

Abstract: PurposeThe purpose of this study is to answer whether and how supervisor–subordinate instrumental or expressive ties based on enterprise social media (ESM) might enhance employee performance.Design/methodology/approachDrawing on social exchange theory, this study developed a theoretical model to explore the influencing mechanism of different supervisor–subordinate ties based on ESM on employee job performance. The model was empirically tested through 219 ESM users.FindingsThe results revealed that supervisor–s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
6
0
1
Order By: Relevance
“…The literature review revealed several interesting antecedents that link to ESM use, such as – transformational leadership (Men, 2014), network sharing (Kwahk and Park, 2016), workplace conflict (Pitafi et al ., 2018; Pitafi et al ., 2020a), psychological safety (Pitafi et al ., 2019), newcomers' work-related use of ESM (Sun et al. , 2019b), supervisor–subordinate ties based on ESM (Wang et al. , 2022a), intrinsic motivation (Yousaf et al ., 2022), and citizenship behaviors (Caya and Mosconi, 2022) – to name a few.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review revealed several interesting antecedents that link to ESM use, such as – transformational leadership (Men, 2014), network sharing (Kwahk and Park, 2016), workplace conflict (Pitafi et al ., 2018; Pitafi et al ., 2020a), psychological safety (Pitafi et al ., 2019), newcomers' work-related use of ESM (Sun et al. , 2019b), supervisor–subordinate ties based on ESM (Wang et al. , 2022a), intrinsic motivation (Yousaf et al ., 2022), and citizenship behaviors (Caya and Mosconi, 2022) – to name a few.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many performance-related outcomes were also identified, such asjob performance (Kwahk and Park, 2016;Shang et al, 2022), task performance (Deng et al, 2020), employee performance (Wang et al, 2022a), employee productivity (Wu, 2013;Wu et al, 2021), employee efficiency (Wu et al, 2021), creative performance (Sun et al, 2020), employee creativity (Pitafi et al, 2020a, b;Wang et al, 2021) and employee agility (Cai et al, 2018;Pitafi et al, 2018Pitafi et al, , 2019Pitafi et al, , 2020bPitafi and Ren, 2021) to name a few.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Asimismo, C. Wang, T. Yuan y J. Feng [16]en su investigación se pudo comprobar que la gestión de un líder, involucrada con la misión de mejorar las habilidades y motivación de los colaboradores, beneficia directamente a la empresa.…”
Section: B Clima Organizacionalunclassified
“…Previous research has found the facilitating role of ESM use on job performance (e.g. Chu, 2020;Deng et al, 2021;Ma et al, 2022;Wang et al, 2022;Wu et al, 2021). More specifically, researchers have noted that ESM use increases individual meta-knowledge, thus promoting job performance (Leonardi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some studies have failed to find a positive relationship between ESM use and job performance (e.g. Brooks, 2015;Lu et al, 2015;Wang et al, 2022). However, these studies have not explained why ESM use decreases job performance.…”
Section: Introductionmentioning
confidence: 99%